Family Dynamics During Emerging Adulthood: Reviewing, Integrating, and Challenging the Field. Issue 3 (31st August 2020) - Oliveira, Carolina; Fonseca, Gabriela; Sotero, Luciana; Crespo, Carla; Relvas, Ana Paula
Abstract : The present study seeks to review and integrate evidence from the empirical literature on family dynamics during the emerging adulthood years. Fifty studies were analyzed, resulting in the following research findings: (a) Emerging adulthood is a period of change in family relationships; (b) family systems anchor both individual and family development during emerging adulthood years; (c) reports of family dynamics by parents and children suggest intergenerational differences; (d) feeling "in between" is not only a characteristic of individuals but also a family experience; and (e) individual‐ and family‐level sociodemographic indicators shape family dynamics in emerging adulthood. The main challenges for future research entail considering the family as the unit of analysis by collecting data from multiple family members, conducting longitudinal studies to better understand changes in family relationships across emerging adulthood, and focusing on family relationships beyond the parent–child dyad.